Cost of high prevalence mental disorders: Findings from the 2007 Australian National Survey of Mental Health and Wellbeing. (December 2017) - Lee, Yu-Chen; Chatterton, Mary Lou; Magnus, Anne; Mohebbi, Mohammadreza; Le, Long Khanh-Dao; Mihalopoulos, Cathrine
Objective: The aim of this project was to detail the costs associated with the high prevalence mental disorders (depression, anxiety-related and substance use) in Australia, using community-based, nationally representative survey data. Methods: Respondents diagnosed, within the preceding 12 months, with high prevalence mental disorders using the Confidentialised Unit Record Files of the 2007 National Survey of Mental Health and Wellbeing were analysed. The use of healthcare resources (hospitalisations, consultations and medications), productivity loss, income tax loss and welfare benefits were estimated. Unit costs of healthcare services were obtained from the Independent Hospital Pricing Authority, Medicare and Pharmaceutical Benefits Scheme. Labour participation rates and unemployment rates were determined from the National Survey of Mental Health and Wellbeing. Daily wage rates adjusted by age and sex were obtained from Australian Bureau of Statistics and used to estimate productivity losses. Income tax loss was estimated based on the Australian Taxation Office rates. The average cost of commonly received Government welfare benefits adjusted by age was used to estimate welfare payments. All estimates were expressed in 2013–2014 AUD and presented from multiple perspectives including public sector, individuals, private insurers, health sector and societal. Results: The average annual treatment cost for people seeking treatment was AUD660 (public), AUD195 (individual), AUD1058 (private) and AUD845 from the health sector's perspective. The total annual healthcare cost was estimated at AUD974m, consisting of AUD700m to the public sector, AUD168m to individuals, and AUD107m to the private sector. The total annual productivity loss attributed to the population with high prevalence mental disorders was estimated at AUD11.8b, coupled with the yearly income tax loss at AUD1.23b and welfare payments at AUD12.9b. Conclusion: The population with high prevalence mental disorders not only incurs substantial cost to the Australian healthcare system but also large economic losses to society.